PENGARUH SELF INSTRUCTIONAL MODULE (SIM) TERHADAP SELF CONFIDENCE DAN LABORATORIUM SKILL DALAM AIRWAY MANAGEMENT - Imardiani; Eric Maulana1; Muhammad Aditya (HEALTH CARE: JURNAL KESEHATAN, 2025)
Introduction. Poisoning education is a process that nursing students must go through to become skilled and professional health workers. Abortion education can be conducted in the classroom or in the laboratory before undergoing clinical practice. Increasing self-confidence and skills (laboratory skills) can be done by providing education with appropriate methods, one of which is by using the self-instructional module (SIM) learning method. Emergency problems that are often encountered in the practice are airway problems. This condition requires nursing students to know and be able to provide actions in emergency conditions, namely maintaining the patient's breathing. Good self-confidence and skills will affect student performance later in facing a real emergency environment. Objective: Knowing SIM can increase self-confidence and laboratory skills related to the implementation of airway management in students with bleeding. Method: A pre-experimental study with a pretest posttest design approach, involving 28 respondents selected by consecutive sampling. The research instrument used an e-module airway management, a self-confidence questionnaire and observation sheets for the implementation of head tilt chin lift, jaw thrust, OPA installation, NPA, and suction. Results: Both self-confidence and laboratory skills showed an effect after the SIM intervention, with a p-value of 0.032 for self-confidence and 0.001 for laboratory skills (head tilt chin lift, jaw thrust, OPA insertion, NPA insertion, and suction). Conclusion: Based on the results, SIM can be a learning method for nursing students in learning airway management.